Anxiety and Comorbidities Differences in Adults with Chronic Pulmonary Diseases: Serbian Single Center Experience - Natasa Mujovic; Kristina Popovic; Jelena Jankovic; Snezana Popovac Mijatov; Nebojsa Mujovic; Jelena Bogdanovic; Mihailo Stjepanovic; Ljubica Nikcevic; Natasa Radosavljevic; Dejan Nikolic (Medicina, 2022)
Background and objectives: The purpose of this study is to investigate the differences in the degree of the anxiety and comorbidity levels in patients with different chronic pulmonary diseases such as chronic obstructive bronchitis (COPD) without emphysema phenotype, pulmonary emphysema, bronchial asthma and lung cancer. Materials and Methods: The prospective clinical study included 272 patients that were diagnosed and treated of pulmonary pathology. COPD (without emphysema phenotype) (Group-1), pulmonary emphysema (Group-2), bronchial asthma (Group-3) and lung cancer (Group-4) were assessed. For the evaluation of the anxiety degree, we used Hamilton Anxiety Rating Scale (HAM-A). Results: The degree of cardiovascular symptoms was significantly higher in Group-1 versus Group-2 (p < 0.001), Group-3 (p = 0.001) and Group-4 (p = 0.013), and significantly higher in Group-4 versus Group-2 (p = 0.046). The degree of respiratory symptoms was significantly higher in Group-1 versus Group-2 (p < 0.001), Group-3 (p < 0.001) and Group-4 (p = 0.002), and significantly higher in Group-4 versus Group-2 (p = 0.013) and versus Group-3 (p = 0.023). For gastrointestinal symptoms, the degree of one was significantly higher in Group-1 versus Group-2 (p < 0.001), Group-3 (p < 0.001) and Group-4 (p = 0.017). Somatic subscale values were significantly higher in Group-1 versus Group-2 (p < 0.001), Group-3 (p < 0.001) and Group-4 (p = 0.015), and significantly higher in Group-4 versus Group-2 (p = 0.024). Total HAM-A score was significantly higher in Group-1 versus Group-2 (p = 0.002) and Group-3 (p = 0.007). Conclusions: Patients with COPD (without emphysema phenotype) followed by the lung cancer are at elevated risk of being more mentally challenged in terms of increased anxiety. Furthermore, patients with exacerbation of evaluated pulmonary pathologies have various levels of comorbidities degrees.